Pengaruh Modal Kerja, Biaya Operasioanal, Biaya Promosi, Dan Penjualan Terhadap Laba Bersih: (Studi Kasus pada Perusahaan Sub Sektor Farmasi yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2022) - Shabrian, Mochammad; Hamdani, Deni (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
This study seeks to examine the impact of various factors, including working capital, operating expenses, promotional expenses, and sales, on the net profit of pharmaceutical companies on the Indonesia Stock Exchange from 2015 to 2022. Using secondary data taken from the financial statements of pharmaceutical companies listed on the Indonesia Stock Exchange, this study utilized multiple regression analysis facilitated by statistical software. The findings indicated that working capital, operating expenses, and promotional expenses exerted a significant positive influence on net profit, while sales showed no significant influence on net profit. However, collectively, all the variables examined in this study contributed to 93.3% of the variance in net profit, highlighting their important role in determining the net profit of pharmaceutical companies. These results underscore the importance of effectively managing working capital, operating expenses, and promotional expenses to improve the financial performance of pharmaceutical companies. From a practical standpoint, this study underscores the importance for pharmaceutical management to develop strategies that focus on optimizing working capital, operational efficiency, and promotional expenses to improve net profit and overall financial performance. Therefore, this study enriches the understanding of the factors that influence the financial performance of pharmaceutical companies in the Indonesian capital market.